MgB2/NaNO2-PVA free-standing polymer composite film as a green firework: a step towards environmental sustainability - Jeyavani, Vijayakrishnan; Kumar, Rajendra; Joy, Pattayil Alias; Mukherjee, Shatabdi Porel (Bulletin of Materials Science, 2022)
We have demonstrated a simple fabrication methodology of free-standing polymer composite film firework that sparkles, provides colour display and moderate sound, yet is less polluting. The polymer composite film fireworks are composed of magnesium boride (MgB2), sodium nitrite (NaNO2) and poly(vinyl alcohol) (PVA). This study also suggested that a flammable, explosive powder composition can be made of two very common inorganic precursors, mainly NaNO2 and MgB2 . This is the first report demonstrating composite film fireworks with new flammable composition using metal boride as a primary precursor, which can also be used in conventional fireworks fabrication, replacing the traditional fuel, mainly gunpowder. The film fireworks were free from charcoal, sulphur, metal powder and paper. Therefore, they substantially lower the odour and COx, NOx, emissions and minimize the substantial trash generated when burned. Most importantly, film firework's minimum ignition temperature and exothermic decomposition temperature are much higher than the ambient temperature; hence are safe to handle.
Keywords: Firework; free-standing film; magnesium boride (MgB2); poly(vinyl alcohol) (PVA); sodium nitrite (NaNO2)